Nutrition education intervention improves medical students' dietary habits and their competency and self-efficacy in providing nutrition care: A pre, post and follow-up quasi-experimental study - Amoore, Bright Yammaha; Gaa, Patience Kanyiri; Amalba, Anthony; Mogre, Victor (Frontiers in Nutrition, 2023)
Objective Most doctors and medical students report inadequate competencies in nutrition care. We evaluated the impact of a nutrition education intervention on medical students' lifestyle habits, dietary diversity, nutrition care knowledge, attitude toward nutrition care, and their level of self-efficacy in the provision of nutrition care. Methods All 2nd-year medical students were enrolled into a 5 week, 24-h nutrition education intervention that involved both deductive and practical sessions. Pre-, post and 4 weeks follow-up assessments were conducted. Results At post- and 4-weeks post-intervention the number of days participants consumed vegetables and engaged in moderate-to-vigorous physical activity significantly (p = 0.003 and 0.002) improved respectively from baseline. Mean nutrition care knowledge scores of participants increased by 3.27 points (95% Cl: 1.98–4.56, p < 0.001) from 19.49 at baseline through to 24.78 post- and 22.76 4 weeks follow-up. No significant [X(2)2 = 1.568, p = 0.457] change in mean attitude toward nutrition care score was recorded. Mean level of self-efficacy in the provision of nutrition care improved significantly by 1.73 (95% Cl: 1.17–2.28, p < 0.001) at post-intervention and 4 weeks follow-up compared to the baseline scores. Conclusion The intervention improved the nutrition care knowledge, self-efficacy in the provision of nutrition care as well as medical students' own consumption of vegetables, dietary diversity and their engagement in moderate-to-vigorous physical activity. However, continuous implementation of nutrition education interventions is needed to sustain these outcomes and further improve the nutrition education experience of medical students.